Maksim Relevansi pada Film “Calon Lurah” Karya Hajar Pamuji (Tinjauan Pragmatis) - Windha Pradhita Citra Yuli Hapsari; Surana Surana (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This study aims to analyze the application of the maxim of relevance in the film "Calon Lurah" by Hajar Pamuji using a pragmatic approach and descriptive qualitative methods. The focus of this research is on the dialogues between the characters in the film, which demonstrate adherence to the cooperative principle and the maxim of relevance, where each speaker's contribution is relevant to the topic or context of the conversation. Three main types of utterances were found in this study: assertive, directive, and expressive utterances. Assertive utterances express something that the speaker believes to be a fact, while directive utterances aim to get the listener to do something, and expressive utterances convey the speaker's feelings or emotions. Primary data for this study was taken from transcribed dialogues in the film, while secondary data came from various sources such as books, journals, theses, and related research. Data collection techniques included observing and noting. The results showed that the film "Calon Lurah" effectively applies the maxim of relevance in the dialogues between its characters, making the conversations relevant and supporting the cooperative principle in communication. This research highlights the importance of relevance in communication to ensure effective and efficient conversations and underscores the practical application of this concept in various communication contexts.